EVALUASI KUALITAS LAYANAN WEBSITE PUSDIKLAT BPK RI MENGGUNAKAN METODE WEBQUAL MODIFIKASIAN DAN IMPORTANCE PERFORMANCE ANALYSIS - Bayu Luhur Wicaksono; Adhi Susanto; Wing Wahyu Winarno (MEDIA, 2012)
This study tries to evaluate the service quality of Pusdiklat BPK RI website user perceptions measured by modification approach webqual variables. This evaluation also focuses on the extent to which perceptions of website service quality perceived by the level of expectation from the perspective of service users Pusdiklat BPK RI website. This research takes an object on a website that addresses Pusdiklat BPK RI in www.pusdiklat.bpk.go.id with 155 respondents in the sample used in the measurement of the quality of service of this website. The method used to evaluate the integration of the calculation approach webqual variable modifications within the framework of Structural Equation Modelling(SEM)and Importance Performance Analysis (IPA). The results of this research, that there is a positive and significant relationship between the variables of website service quality, satisfaction levels, and the intensity of use of that form a conceptual model of research. To improve user satisfaction and loyalty for services rendered to maintain the consistency of the performance of some of the attributes of the perceptual interaction and information that has the greatest contribution to the quality of the service website. While the attributes that are necessary to get attention is a matter of updating the content information and access response time on the look of the website. The results are expected to provide feedback to management (team manager)Â  Pusdiklat BPK RI website service in the improvement and development of the website to match user expectations.